HUBUNGAN KARAKTERISTIK INDIVIDU, BEBAN KERJA, DAN KUALITAS TIDUR DENGAN KELELAHAN KERJA PADA TENAGA KEPENDIDIKAN DI INSTITUSI KEPENDIDIKAN X - Dionisius Indra Prakoso; Yuliani Setyaningsih; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2018)
Fatigue is a protective mechanism for the body to avoid damage so that recovery can occur after resting. Workload is the body of the worker in accepting the work. Sleep quality is a person's satisfaction with sleep. The purpose of this study is to analyze the relationship between individual characteristics, workload, quality of sleep with work fatigue on educational personnel. This study uses cross sectional study which is a form of observational study and is analytic descriptive. The sample of this research is 44 person of educational staff with total sampling sampling method. data retrieval of fatigue was measured using reaction timer, physical load using the 10 pulse method with stopwatch, and other variables using questionnaire Statistical analysis using Rank Spearman correlation test. The results showed no relationship between smoking habits (p=0,800) and physical workload (p=0,141) with work fatigue. There is a relationship between years of service (p=0,026), mental burden (p=0,032), and sleep quality (p=0,031) with work fatigue.